2020
DOI: 10.1007/s10539-020-09772-0
|View full text |Cite
|
Sign up to set email alerts
|

Unlimited Associative Learning and the origins of consciousness: a primer and some predictions

Abstract: Over the past two decades, Ginsburg and Jablonka have developed a novel approach to studying the evolutionary origins of consciousness: the Unlimited Associative Learning (UAL) framework. The central idea is that there is a distinctive type of learning that can serve as a transition marker for the evolutionary transition from non-conscious to conscious life. The goal of this paper is to stimulate discussion of the framework by providing a primer on its key claims (Part I) and a clear statement of its main empi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(68 citation statements)
references
References 65 publications
(76 reference statements)
2
55
0
Order By: Relevance
“…The current account may also provide a fuller picture of why ‘unlimited associative learning’—due to facilitating the complex reafferent processes associated with a deep self-model—may be a marker of the evolutionary transition to minimal consciousness ( Bronfman et al. 2016 ; Ginsburg and Jablonka 2019 ; Birch et al. 2020 ).…”
Section: Consciousness In Other Systemsmentioning
confidence: 95%
“…The current account may also provide a fuller picture of why ‘unlimited associative learning’—due to facilitating the complex reafferent processes associated with a deep self-model—may be a marker of the evolutionary transition to minimal consciousness ( Bronfman et al. 2016 ; Ginsburg and Jablonka 2019 ; Birch et al. 2020 ).…”
Section: Consciousness In Other Systemsmentioning
confidence: 95%
“…Further, principles of association may be surprisingly powerful if they are capable of representing specific relational structures as particular graphs/networks, which are increasingly being recognized as powerful learning and inferential systems (Gentner, 2010;Zhou et al, 2019;Crouse et al, 2020). Some have even suggested that the spatial and temporal mapping abilities of the H/E-S represent a special case of general purpose unlimited associative learning (Birch et al, 2020), such as aggregation across episodes (Mack et al, 2018(Mack et al, , 2020Mok and Love, 2019), or of dynamically evolving graphs capable of generating cognitive maps via representational "cloning" (Gothoskar et al, 2019). The central role of the H/E-S for higher-order cognition is further understandable in light of the fact that many (and possibly most) aspects of intelligence can be described as search processes (Conant and Ashby, 1970;Hills et al, 2010), which might be even more clearly apparent if we think of the possibility of spatializing abstract domains such as complex feature spaces (Eichenbaum, 2015;Whittington et al, 2018), or even time (Howard, 2018;Gauthier et al, 2019).…”
Section: H/e-s As Orchestrator Of High-level Cognitionmentioning
confidence: 99%
“…Our definition of “complex operant learning” was initially rather vague, but it came to mean learning many new survival behaviors from experience based on rewards and punishments [ 72 ]. Now, in my opinion, it is stated even better in the Unlimited Associative Learning (UAL) concept of Ginsburg and Jablonka [ 41 ], which was recently upgraded [ 90 ] as follows: UAL says an animal is conscious if it can learn from compound, novel stimuli; learn from what it already has learned and then do so again and again; learn by trace conditioning; and perform “valence switching,” meaning the animal can learn to like (approach) what it formerly disliked (avoided) and vice versa.…”
Section: Neurobiological Naturalism and Iitmentioning
confidence: 99%